2017
DOI: 10.20343/teachlearninqu.5.1.8
|View full text |Cite
|
Sign up to set email alerts
|

How Experienced SoTL Researchers Develop the Credibility of Their Work

Abstract: Teaching and learning research in higher education, often referred to as the Scholarship of Teaching and Learning (SoTL), is still relatively novel in many academic contexts compared to the mainstay of disciplinary research. One indication of this is the challenges those who engage in SoTL report in terms of how this work is valued or considered credible amongst disciplinary colleagues and in the face of institutional policies and practices. This paper moves beyond the literature that describes these specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Teaching and learning are scholarly activities, and both are closely related to assessment and understanding. As Felten (2013) argues, knowledge about, and experiences from such scholarly activities need to be shared in order to be understood as significant intellectual work in academia (see also Billot et al 2017). There is, of course, an alternative and quite legitimate view saying that changes are most effective if and when they are implemented at a general level.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching and learning are scholarly activities, and both are closely related to assessment and understanding. As Felten (2013) argues, knowledge about, and experiences from such scholarly activities need to be shared in order to be understood as significant intellectual work in academia (see also Billot et al 2017). There is, of course, an alternative and quite legitimate view saying that changes are most effective if and when they are implemented at a general level.…”
Section: Discussionmentioning
confidence: 99%
“…SoTL practitioners still bemoan the scarcity of time and resources, the difficulty in finding like-minded colleagues, particularly within their own institutions, and the lack of recognition and value attributed to SoTL work. In addition, Billot, Rowland, Carnell, Amundsen, and Evans (2017) indicated that the expectations around SoTL research at tertiary institutions were not always clearly defined and that participants struggled with the perceptions of the lack of credibility mirrored to SoTL work. Along with the barriers of being a SoTL researcher, participants also reported significant hurdles when attempting SoTL including a lack of funds, the time to complete applications, and finding scholarly journals to publish SoTL research.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…SOTL credibility has previously been found to be linked to publications and citations (Billot et al 2017) despite it offering a seemingly limitless range of outlets and opportunities to display impact. This has led to ongoing uncertainty around the appropriate means for sharing SOTL work (Felten 2013).…”
Section: In Search Of a Definition Of Scholarshipmentioning
confidence: 99%
“…The ambiguity in definition and understanding of scholarship (Fanghanel et al 2016) leads to differences in perception of the nature and evaluation of scholarship work (Billot et al 2017), impacting both career progression and orientation of scholarship activities. As education-focused academic roles continue to grow as a share of the academic workforce (HESA 2021a), role descriptions and promotion criteria have been developed to provide full career pathways from entry-level to professor.…”
Section: Introductionmentioning
confidence: 99%